Temporal variation of fish and shrimp assemblages in Merbok river estuary, Tanjung Dawai, Kedah - Azizan, Anas Al-Ansari (2012)
The temporal variation and assemblage composition of fish and shrimps species caught by estuarine set bag net (ESBN) in Tanjung Dawai estuarine, Tanjung Dawai, Kedah, Malaysia were investigated based on the data from May to September 2012. Stolephorus tri was the most abundant fish caught by ESBN in Tanjung Dawai (1.1%), while Acetes sp. was the most abundant shrimps (92.18%). The highest percentage of species occurrence caught by ESBN in Tanjung Dawai estuary was found in August (70.0%), and the lowest was in May (50%). The percentage of numerical abundance of all fish and shrimp species caught by ESBN was the highest in July (51.17%) and the lowest in August (7.04%). The length-weight relationship analysis displayed that four species have a positive allometric growth and seven of them have a negative allometric growth. The average monthly catch per unit effort (CPUE) of the ESBN observed was 2.914 kg/net/hour. Since that the abundance percentage of juvenille fish caught by ESBN is low (2.42%), the use of ESBN in Tanjung Dawai estuarine, Merbok River, Kedah was concluded as a a non-destructive fishing gear.